Gilli danda to golf : a memoir - Varma, Ram (New Delhi Rupa, 2021)
Profound, introspective and a no-holds-barred life story of a seasoned bureaucrat His father was a stonemason and his childhood was spent in dusty environs with unshapely stones to play with. But the young boy was not destined to remain uneducated and poor. He went to school, then college, became a lecturer and finally qualified for the most coveted government service in the country, the Indian Administrative Services. Serving under various capacities under the three Lals of Haryana$1 (BBansi, Devi and Bhajan Lal$1 (BRam Varma$1 (Bs memoir records the ups and downs of a meaningful and fulfilling career. Spanning from his childhood days spent in the rural terrains of Rajasthan playing gillidanda to swooshing the golf clubs amidst the green expanse of a golf course, From Gillidanda to Golf is a deeply personal account of an IAS officer, peppered with anecdotes and incidents making this book a beautiful tribute to life.s
Keywords: IAS as an author; Golf; Memoir